The effect of high altitude on ephedrine content and metabolic variations in two species of Ephedra - Lu, Mengnan; He, Wenjia; Xu, Ziyan; Lu, Yan; Crabbe, M. James C.; De, Ji (Frontiers in Plant Science, 2023)
Ephedra is an important plant in Chinese medicine; however, there are few reports on two species of Ephedra which are distributed at high altitudes from 3000 to 5200 meters. We collected a total of 84 individuals representing five Ephedra gerardiana and nine Ephedra saxatilis populations respectively located from 3158 to 5200 meters altitude, and determined the relative content of 213 metabolites using UHPLC-MS/MS (Ultra-High-Performance Liquid Chromatography-tandem mass spectrometry). 37 Chemical compositions were annotated using the KEGG (Kyoto Encyclopaedia of Genes and Genomes) database. From the top five significant enrichments in metabolic KEGG pathway analysis, we found a total of 166 compounds belonging to phenylpropanoids, 123 flavonoids, 67 metabolites carried by ABC transporters, and 61 in purine metabolism. We identified the top 8 altitude-related compounds in two species. Ephedrine and pseudoephedrine were found to be associated with altitude in both E. saxatilis and E. gerardiana.To verify which environmental factors influenced the metabolic content, the soil 2 moisture and temperature of each population site were collected, and quantitative analysis of ephedrine and pseudoephedrine was performed using UHPLC-MS (Ultra-High-Performance liquid chromatography-tandem mass spectrometry). After detection, soil moisture ranged from 0.074 to 0.177 mm 3 /mm 3 , and temperature ranged from 9.7℃ to 23.9℃. The content of ephedrine ranged from (0.84±0.49)% to (2.01±0.41)% in E. saxatilis, which was positively correlated with soil moisture; the content of pseudoephedrine ranged from (0.72±0.45)% to (1.11±0.57)% and was negatively correlated with soil moisture. In contrast to these results, in E. gerardiana, the content of ephedrine and pseudoephedrine was negatively correlated with soil moisture. Furthermore, the trends of alkaloid contents in two kinds of Ephedra were similar when the temperature was lower than 17℃ even if the sum was various. With the increase in soil moisture and temperature, the total alkaloid content of E. saxatilis was higher than that of E. gerardiana. When the soil moisture was lower, the alkaloid content of the two Ephedra species was higher. These results provide useful data for the future separation of new compounds, and for seed homogeneous growth to determine artificial breeding of Ephedra located at high altitudes.